Analysis of elite male and female biathlon performances (2009/10 to 2016/17) - Lunghi, A. (Universität Lausanne, 2018)
Biathlon is a complex sport subjected to large performance variability. The analysis and extrapolation of the factors affecting prone or standing shooting and skiing world-class biathlon performances can therefore help improving the training programs according to the biathletes` specific needs. Methods: The analysis comprises data from IBU Cup, IBU World Cup, IBU World Championships and Olympic Winter Games over eight years from season 2009/10 to 2016/17. The research includes sprint, individual, pursuit and mass start competitions for both elite men and women. Factors such as ranking variability, gender, age, type of event, altitude, head-to-head versus individual shooting and shooting progression and the overall best contemporary biathletes` performances have been investigated through data-crossing. Results: The ranking variability goes down to a ratio of 1.2 medals per biathlete in the male individual discipline. Gender shooting performances are very similar; however, women seem to mature earlier and reach the optimal performances later than men, not only for shooting performances but also skiing speed and ranking averages. Age plays an important role in all the performances; for example, 17 year old male biathletes have an average of proportional hit 23% inferior to 35 year olds. IBU Cup performances are lower than IBU World Cup ones from 3.6% to 6.0% in average. Performances can be deteriorated by altitude up to 2.8%. Male Top-30 headto-head shootings are 2.2% lower than individual shootings. The overall shooting performances follow a slender but continuous improvement, in all competitions, ranking groups and genders; the shooting average amelioration between the 8 seasons is of 1.3%. Discussion: Biathletes` have specific performance trends according to gender and age, altitudes over 1400 m deteriorate both shooting and skiing performances and shooting performances degrade with head-to-head confrontation. These findings should be taken into account in the biathletes` training plans.